Football, alcohol and domestic abuse - Ivandic, Ria (2021)
We study the role of alcohol and emotions in explaining the dynamics in domestic abuse following major football games. We match confidential and uniquely detailed individual call data from Greater Manchester with the timing of football matches over a period of eight years to estimate the effect on domestic abuse. We first observe a 5% decrease in incidents during the 2-hour duration of the game suggesting a substitution effect of football and domestic abuse. However, following the initial decrease, after the game, domestic abuse starts increasing and peaks about ten hours after the game, leading to a positive cumulative effect. We find that all increases are driven by perpetrators that had consumed alcohol, and when games were played before 7pm. Unexpected game results are not found to have a significant effect